Die Boden-Staat Relation in Friedrich Ratzels politisch-geographischer Lehre. - Ioannis Mazis; Alekos Stogiannos (Zeitschrift für die Regionale Wissenschaft., 2011)
The paper aims to point out some of the relations between land and state in Friedrich Ratzel political-geographic analysis. First, it will be demonstrated how the perception of the land correlates with the culture situation of the observer. Second, it will be shown how political space is situated in Ratzel’s analytical system of power. At last it will be examined how far Ratzel estimates both, geographical and human factors, in his political system and decision making process.